2022
DOI: 10.32468/be.1209
|View full text |Cite
|
Sign up to set email alerts
|

Is the Covid-19 Pandemic Fast-Tracking Automation in Developing Countries? Evidence from Colombia

Abstract: This paper assesses whether the Covid-19 pandemic accelerated automation in developing countries. We studied the case of Colombia, a country with low R&D and productivity and with high labor informality and unemployment. We estimated event-study models to assess the differential effect of the pandemic on job openings and salaried employment by the potential degree of automation of each occupation. Our results suggest that both vacancies and salaried employment fell more in highly automatable occupations du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
2
0
2
Order By: Relevance
“…Sin embargo, con la crisis de la pandemia del COVID-19, el sistema de salud en Colombia se fortaleció para atender la emergencia sanitaria porque hubo inversión en la modernización de los hospitales, en el desarrollo de protocolos de bioseguridad y en la innovación digital, la cual se ha acelerado debido al confinamiento con la utilización de aplicaciones de industria 4.0. Esto ha permitido reducir los desplazamientos y llevar al paciente diagnósticos, intervenciones y seguimientos de manera remota a sus lugares de origen y repensar el modelo de turismo (Bonilla-Mejía et al, 2022;ONU, 2020; Pulido Arbeláez y Cabello Beltrán, 2020; Rodríguez-Jiménez y Martínez-Martínez, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, con la crisis de la pandemia del COVID-19, el sistema de salud en Colombia se fortaleció para atender la emergencia sanitaria porque hubo inversión en la modernización de los hospitales, en el desarrollo de protocolos de bioseguridad y en la innovación digital, la cual se ha acelerado debido al confinamiento con la utilización de aplicaciones de industria 4.0. Esto ha permitido reducir los desplazamientos y llevar al paciente diagnósticos, intervenciones y seguimientos de manera remota a sus lugares de origen y repensar el modelo de turismo (Bonilla-Mejía et al, 2022;ONU, 2020; Pulido Arbeláez y Cabello Beltrán, 2020; Rodríguez-Jiménez y Martínez-Martínez, 2022).…”
Section: Discussionunclassified
“…Para la recuperación en la postpandemia, según el CONPES (2021), en el año 2020 el PIB se contrajo alrededor del 6,8% y se recupera el 5% en el año 2021. En este escenario, la política para la reactivación económica en el corto plazo se enfoca en desarrollar las capacidades en los hogares, el aparato productivo y el desarrollo digital para que en el largo plazo se encamine hacia un desarrollo sostenible (Bonilla-Mejía et al, 2022;Consejo Privado de Competitividad, 2020;CONPES, 2021;Pulido Arbeláez y Cabello Beltrán, 2020). Para Bogotá, la ciudad más grande del país y principal destino del turismo de salud, se contemplan acciones concretas para la reactivación de la empresa con reducción fiscal, sofisticación con tecnología, negocios verdes e industrias culturales y creativas (Alcaldía Mayor de Bogotá, 2020).…”
Section: Proveedoresunclassified
“…For Chile, a developing economy, Egana-delSol et al (2022) find that the outbreak of the pandemic reduced employment in occupations more prone to automation at the industry level, though they do not differentiate between paralyzed and essential jobs. Additionally, Bonilla-Mejía et al (2022) find that the pandemic reduced job openings and employment in highly automatable occupations in Colombia, using occupation-city-level data.…”
Section: Introductionmentioning
confidence: 95%
“…Pandemic-related mobility restrictions can be interpreted as a sudden and exogenous increase in labor costs (Bonilla-Mejía et al, 2022), which can increase the returns to adopting technology and automating jobs. For instance, according to a World Economic Forum (2020) survey, after the pandemic broke out, around 50% of business leaders were set to accelerate the automation of jobs in their companies, and 43% of businesses indicated that they were set to reduce their workforce because of technology integration.…”
Section: Introductionmentioning
confidence: 99%